Current research status of Traditional Chinese Medicine nursing for patients with sleep disorder after stroke (脑卒中后睡眠障碍中医护理技术研究现状) - HU Haixia (胡海霞); LIANG Haiyun (梁海云); HAN Xuelian (韩雪莲); XIE Ying (谢影); LI Yanmei (李艳梅) (中西医结合护理)
Sleep disorder is a common complication of stroke, which not only negatively affects the patients’ quality of life, but also affects the rehabilitation process of stroke disease. There are many causes of post-stroke sleep disorders, including clinical medication, patients' own psychological factors, pathological damage, etc. From the perspective of Traditional Chinese medicine nursing and analysis of actual situation of patients with post-stroke sleep disorders, this study reviewed the studies on Traditional Chinese Medicine nursing for patients with sleep disorder after stroke, and provided reference for clinical decision making and nursing practice. (睡眠障碍是脑卒中患者较为常见的一种并发症, 不仅影响患者生活质量, 且不利于脑卒中后期康复。脑卒中后患者并发睡眠障碍与临床用药、患者自身心理因素、病理损害等有关。本研究从中医护理的角度进行分析, 结合脑卒中后睡眠障碍患者实际情况, 就脑卒中后睡眠障碍患者的中医护理研究现状进行综述, 旨在为临床制定相关干预方案提供参考与借鉴。)